In vitro micropropagation protocols for two endangered Dianthus species - via in vitro culture for conservation and recultivation purposes - Dóra Farkas; Judit Csabai; Angéla Kolesnyk; Pál Szarvas; Judit Dobránszki (Plant Methods)
Abstract Background D. giganteiformis subsp. pontederae and D. superbus subsp. superbus are protected or critically endangered species in several European regions; therefore, developing an efficient in vitro micropropagation protocol is essential for germplasm conservation and recultivation purposes. Results After germination, one-nodal segments of both species were transferred onto several MS media supplemented with 3% sucrose and different types of cytokinins (at a concentration of 4.5 µM) alongside 0.54 µM 1-naphthaleneacetic acid (NAA) for the multiplication phase for 3 weeks. The shoot clusters were subsequently transferred onto elongation medium (plant growth regulator-free MS medium) for 3 weeks. Individual shoots separated from the shoot clusters were cultured on MS medium supplemented with 0.54 µM NAA and 2% sucrose for 3 weeks for rooting. Taking into account the effects and after-effects of cytokinins, we found that the most suitable cytokinin for D. giganteiformis subsp. pontederae was N-(2-isopentenyl)-adenine (2-iP), while for D. superbus subsp. superbus it was meta-topolin (mT). Conclusions In vitro micropropagation methods were developed for two endangered Dianthus species (D. giganteiformis subsp. pontederae and D. superbus subsp. superbus) by determining the optimal type of cytokinin to be used during the multiplication phase. The protocols are designed to produce large quantities of propagation material for recultivation, educational, and research purposes within three months.